Implementasi Akuntansi Salam dalam Aplikasi Shopee - Rani Rufmana Pohan; Rahmat Daim Harahap; Elvina Damayanti Hrp; Dini Ramdhani; Nia Pefrina; Muhammad Azmi Lubis (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this journal is to analyze and describe the implementation of salam accounting in the Shopee application. Salam accounting is an accounting method used in Islamic commerce that involves salam transactions, namely the sale of goods with payment in advance with future delivery of the goods. The Shopee application is one of the most popular e-commerce platforms in Indonesia and is used by many merchants to sell their products. This journal uses a descriptive-analytical approach to evaluate and understand how greeting accounting is implemented in the Shopee application. The research was conducted through literature studies, document analysis, and interviews with traders using the Shopee application. The results show that Shopee has introduced a salam accounting feature in its application to facilitate salam transactions between sellers and buyers. This feature allows sellers to offer salam products to buyers, who can then make prepayments. After payment is received, the seller will send the goods to the buyer according to the agreement that has been made. In addition, this journal also analyzes the challenges and benefits of implementing salam accounting in the Shopee application. Some of the challenges identified include poor understanding of the greeting accounting concept among traders, and difficulties in managing stock of goods for future deliveries.